Epigenetics in Tuberculosis: Immunomodulation of Host Immune Response - Avinash Khadela; Vivek P. Chavda; Humzah Postwala; Yesha Shah; Priya Mistry; Vasso Apostolopoulos (Vaccines, 2022)
Tuberculosis is a stern, difficult to treat chronic infection caused by acid-fast bacilli that tend to take a long time to be eradicated from the host’s environment. It requires the action of both innate and adaptive immune systems by the host. There are various pattern recognition receptors present on immune cells, which recognize foreign pathogens or its product and trigger the immune response. The epigenetic modification plays a crucial role in triggering the susceptibility of the host towards the pathogen and activating the host’s immune system against the invading pathogen. It alters the gene expression modifying the genetic material of the host’s cell. Epigenetic modification such as histone acetylation, alteration in non-coding RNA, DNA methylation and alteration in miRNA has been studied for their influence on the pathophysiology of tuberculosis to control the spread of infection. Despite several studies being conducted, many gaps still exist. Herein, we discuss the immunopathophysiological mechanism of tuberculosis, the essentials of epigenetics and the recent encroachment of epigenetics in the field of tuberculosis and its influence on the outcome and pathophysiology of the infection.